HUMAN CENTRIC DIGITAL TRANSFORMATION IN SMES: THE ROLE OF DIGITAL COMPETENCE , EMPOWERMENT PSYCHOLOGY AND LEADERSHIP TO WORKFORCE ADAPTABILITY - Ahyani Ridzky Ramadhan; Irsan Tricahyadinata; Wirasmi Wardhani (CV. Radja Publika, 2026)
Digital transformation demands improvement adaptability power work , especially in business small and medium enterprises (SMEs) that have limitations source power . Research This aim test influence digital competence and empowerment psychological to adaptability employees , with consider role moderation characteristics owner business . Using approach quantitative explanatory , data obtained of 334 respondents from the SME sector culinary and analyzed using Structural Equation Modeling – Partial Least Squares (SEM-PLS). The results show that digital competence and empowerment psychological influential positive significant to adaptability , with empowerment psychological as the most dominant determinant . In addition , the characteristics owner proven strengthen second connection the findings . This confirm that adaptability power Work No only determined by capability technical , but also by conditions psychological and contextual leadership . Research This contribute with integrate dynamic capability perspective , Self-Determination Theory, and deep leadership explain adaptability in the context of SMEs, as well as expand human-centric approach in studies digital transformation.